Problematic intervention in the new international order and its impact on international relations - the U.S. role a model (Journal of the College of Education for Women, 2019)
Intervention in International Relations from the concepts that are still highlycontroversial among those he considers a breach of international law and the UN Charter andin violation of the rule , and those who felt that the need provided, however, that this is linkedmotives humanity recognized by the international community , because the internationalvariables proved the inadequacy of the principle of non-interference and the principle ofsovereignty as the traditional variables international , and therefore most of the internationalpractice came a bus with many of the behaviors that reflect a decline in its entirety to theseprinciples , and became adapt these principles with international reality is too complex forbeing susceptible to the interests and priorities of the international.The legal non-intervention in international relations have changed with the change ofthe concept of sovereignty and the internationalization of a lot of issues, including the issue ofhuman rights , hence the advantage of the United States in order to enter and selectively so asto achieve their interests , so the respect for international law in all its principles need toactivate the role of a number of institutions international influence in the face of the parties inthe international community and adjust their behavior